POTENSI HAZARD TERKAIT PEMERIKSAAN ORANG DAN BARANG BAWAAN OLEH PETUGAS AVSEC DI POS 2 SISI UDARA (TERMINAL KARGO) BANDAR UDARA INTERNASIONAL MINANGKABAU - Lintang Adyuta Daniswara; Hemi Pramuraharjo; Ichyu Machmiyana (Journal of Social and Economics Research, 2025)
The rapid growth of the aviation industry has increased the complexity of airport security systems, especially in restricted airside areas. One critical point is Checkpoint 2 at the cargo terminal of Minangkabau International Airport, where manual screening by Aviation Security (Avsec) officers persists without optimal use of supporting equipment such as X-Ray, WTMD, and HHMD. This study aims to identify hazard potentials arising from deviations from the Standard Operating Procedures (SOP) and to evaluate the effectiveness of screening technologies. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation during On the Job Training. Findings reveal that incomplete manual inspections, insufficient personnel, and the non-operational status of security equipment create significant security gaps that threaten flight safety and increase insider threat risks. The study recommends immediate technical verification of security tools, SOP retraining, and staff reinforcement to ensure standardized and effective screening processes. These findings contribute to the development of strategic improvements in air cargo area security.